My Math Forum Separating a Relation into Multiple Functions

 Pre-Calculus Pre-Calculus Math Forum

 June 12th, 2016, 02:35 AM #1 Newbie   Joined: Jun 2016 From: Sol System Three Posts: 5 Thanks: 0 Separating a Relation into Multiple Functions Hi I am reviewing some precalculus material and have run into some thing I am having trouble understanding. The problem is to characterize the relation y^4 - 4y^2 = x^2 + 4x I found x intercept at (0,-4) and y intercepts at (0,0) (0,-2) and (0,2), And determined the relation is symmetric about the x axis. I solved for y and got f1(x) = sqrt( x+4 ) f2(x) = - sqrt( x+4 ) The answer key in the book also lists, f3(x) = sqrt( -x ) f4(x) = -sqrt( -x ) I'm having trouble seeing how to derive f3(x) and f4(x), and the book provides only the function listing without further explanation.
 June 12th, 2016, 03:30 AM #2 Math Team   Joined: Jan 2015 From: Alabama Posts: 3,264 Thanks: 902 I wonder how you got the first two without also seeing the last two! First treat the given equation as a quadratic equation for $\displaystyle y^2$: $\displaystyle (y^2)^2-4(y^2)- (x^2+ 4x)= 0$. Use the quadratic formula to solve that equation: $\displaystyle y^2= \frac{4\pm \sqrt{16+ 4x^2+ 16x}}{2}= \frac{4\pm 2\sqrt{x^2+ 4x+ 4}}{2}$ Of course $\displaystyle x^2+ 4x+ 4= (x+ 2)^2$ so we have $\displaystyle y^2= \frac{4\pm 2(x+ 2)}{2}= 2\pm (x+ 2)$ Taking the positive sign, $\displaystyle y^2= x+ 4$ so $\displaystyle y= \pm\sqrt{x+ 4}$ and taking the negative sign $\displaystyle y^2= -x$ so $\displaystyle y= \pm \sqrt{-x}$. If we are dealing only with real numbers, the first two solutions are valid for all x greater than or equal to -4 and the second two only for x less than or equal to 0. Thanks from Derric Last edited by Country Boy; June 12th, 2016 at 03:33 AM.
 June 12th, 2016, 03:30 AM #3 Global Moderator     Joined: Oct 2008 From: London, Ontario, Canada - The Forest City Posts: 7,932 Thanks: 1127 Math Focus: Elementary mathematics and beyond I list all possible cases: $\displaystyle (y^2-2)^2=(x+2)^2\implies y^2-2=x+2\implies y=\pm\sqrt{x+4}$ $\displaystyle (y^2-2)^2=(-x-2)^2\implies y^2-2=-x-2\implies y=\pm\sqrt{-x}$ $\displaystyle (2-y^2)^2=(x+2)^2\implies 2-y^2=x+2\implies y=\pm\sqrt{-x}$ $\displaystyle (2-y^2)^2=(-x-2)^2\implies 2-y^2=-x-2\implies y=\pm\sqrt{x+4}$ Thanks from Derric
June 12th, 2016, 04:09 AM   #4
Newbie

Joined: Jun 2016
From: Sol System Three

Posts: 5
Thanks: 0

Quote:
 Originally Posted by greg1313 I list all possible cases: $\displaystyle (y^2-2)^2=(x+2)^2\implies y^2-2=x+2\implies y=\pm\sqrt{x+4}$ $\displaystyle (y^2-2)^2=(-x-2)^2\implies y^2-2=-x-2\implies y=\pm\sqrt{-x}$ $\displaystyle (2-y^2)^2=(x+2)^2\implies 2-y^2=x+2\implies y=\pm\sqrt{-x}$ $\displaystyle (2-y^2)^2=(-x-2)^2\implies 2-y^2=-x-2\implies y=\pm\sqrt{x+4}$
This is how I worked the problem, and I see what I missed now. That is:

( y^2 - 2 )^2 = ( +/- ( x+2) )^2

and the subsequent results. All I did was the positive case.

Last edited by Derric; June 12th, 2016 at 04:31 AM.

June 12th, 2016, 04:14 AM   #5
Newbie

Joined: Jun 2016
From: Sol System Three

Posts: 5
Thanks: 0

Quote:
 Originally Posted by Country Boy I wonder how you got the first two without also seeing the last two! First treat the given equation as a quadratic equation for $\displaystyle y^2$: $\displaystyle (y^2)^2-4(y^2)- (x^2+ 4x)= 0$. Use the quadratic formula to solve that equation: $\displaystyle y^2= \frac{4\pm \sqrt{16+ 4x^2+ 16x}}{2}= \frac{4\pm 2\sqrt{x^2+ 4x+ 4}}{2}$ Of course $\displaystyle x^2+ 4x+ 4= (x+ 2)^2$ so we have $\displaystyle y^2= \frac{4\pm 2(x+ 2)}{2}= 2\pm (x+ 2)$ Taking the positive sign, $\displaystyle y^2= x+ 4$ so $\displaystyle y= \pm\sqrt{x+ 4}$ and taking the negative sign $\displaystyle y^2= -x$ so $\displaystyle y= \pm \sqrt{-x}$. If we are dealing only with real numbers, the first two solutions are valid for all x greater than or equal to -4 and the second two only for x less than or equal to 0.
Well, I completed the squares rather than taking this approach. I do like having more than one way to approach a problem.

What I missed would have more easily been seen had I used this method.

Last edited by Derric; June 12th, 2016 at 04:48 AM.

 June 12th, 2016, 04:46 AM #6 Newbie   Joined: Jun 2016 From: Sol System Three Posts: 5 Thanks: 0 I think it's interesting to note I would have expected f3 and f4 to be: +/- sqrt(-x-4) rather then just +/- sqrt(-x). Thus in the interval from 0 to -4 there are four separate functions. I suppose for the purpose of learning math that is irrelevant, although I'm trying to think of an actual case were this equation might be modeling something, then a decision might have to be made which function or pair of functions would be relevant in that interval.
June 12th, 2016, 10:29 AM   #7
Senior Member

Joined: May 2016
From: USA

Posts: 1,310
Thanks: 551

Quote:
 Originally Posted by Derric I think it's interesting to note I would have expected f3 and f4 to be: +/- sqrt(-x-4) rather then just +/- sqrt(-x). Thus in the interval from 0 to -4 there are four separate functions. I suppose for the purpose of learning math that is irrelevant, although I'm trying to think of an actual case were this equation might be modeling something, then a decision might have to be made which function or pair of functions would be relevant in that interval.
Frequently when you are modeling something, there are constraints on the value a valid answer may have. For example, non-negativity constraints are very common. The math may give multiple answers, but the extra constraints imposed by the nature of what is being modeled reduce that number.

 Tags function, functions, multiple, relation, separating

 Thread Tools Display Modes Linear Mode

 Similar Threads Thread Thread Starter Forum Replies Last Post wvoke9 Algebra 3 February 3rd, 2016 07:09 AM Gurasees Singh New Users 1 September 27th, 2014 09:17 AM gelatine1 Algebra 2 August 9th, 2013 02:01 AM krayzblu Applied Math 0 May 4th, 2011 11:13 PM marcoesteves Math Software 4 December 19th, 2010 03:46 PM

 Contact - Home - Forums - Cryptocurrency Forum - Top